(untitled) (Islamic Sciences Journal, 2023)
Praise be to Allah, Lord of the Worlds, and prayers and peace be upon our master Muhammad and all his family and companions, and then; To trace back the path and direction of the author in writing his book shows us his thought, the extent of his intelligence and the method of presenting sciences. As well as the extent of his knowledge, influence and influence on the eminent scholars. And the mind, besides the author did not neglect to help the reader in knowing his path, so he stipulated his methodology in the introduction to his interpretation and explained it here, and there is a method and methodology that the author did not explain, so I explained it and provided it with practical examples from his interpretation.